Electrooptic, pyroelectric, dielectric spectroscopic studies of nematic and twist-bend nematic phases of achiral hockey-shaped bent-core liquid crystal - Vij, Jagdish; Panarin, Yuri; Yadav, Neelam (My University, 2022)
Experimental and theoretical investigations of the twist-bend nematic (NTB) phase in liquid crystals have recently received significant attention for reasons of unusual and interesting characteristics of the NTB. Though NTB was predicted to exist for rigid bent-core LCs by Ivan Dozov in 2001, nevertheless it has unambiguously been proven to exist only in a few bent-core systems so far. Here the characteristics of both the nematic (N) and NTB phases are investigated for a hockey shaped achiral rigid bent-core LC, called BCI, in planar and homeotropic aligned cells, using polarizing optical microscopy, electro-optics, pyroelectricity and wide band dielectric spectroscopy. Spontaneous polarization measured for a bias field of 2.2 V/μm of a chiral domain using the pyroelectric effect is found to be only ∼5 nC/cm2. A measurement of the spontaneous polarization using pyroelectricity in general is unaffected by the sample’s dc conductivity except when its conductance dominates the admittance. As helix of NTB is partially unwound by the field, results lead to the identification of NTB as polar and chiral. The first and the second harmonics of the applied field are observed of higher amplitudes in NTB and N phases, respectively. The hockey-shaped bent-core system exhibits a large negative dielectric anisotropy over a wide range of temperatures than observed for any other compound so far. The large negative dielectric anisotropy is the highly desirable characteristic parameter of the NTB for exploring the field induced phases at relatively lower field strengths. The orientational order parameter characteristically jumps at the N-NTB transition temperature. The complex dielectric permittivity is measured as a function of frequency in the range 1 Hz to 10 MHz, the analysis of results reveales two collective modes in the dielectric spectra. Amplitude of the lower frequency mode is much higher than of higher frequency, former is assigned to the hydrodynamic mode with z-dependent rotation of the heloconical director ), this in turn involves compression and dilation of the pseudo-layers. The higher frequency mode corresponds to fluctuations of the tilt director and closer to the transition temperature, it exhibits a typical soft mode characteristic feature.
PUBLISHED
Keywords: Twist-Bend Nematic Phase; Bent-Core Liquid Crystals; Electro-optics of Liquid Crystals; Pyroelectricity; Dielectric Spectroscopy; Nanoscience & Materials